ANTIOXIDANT VITAMIN STATUS IN TYPE 1 DIABETES MELLITUS PATIENTS - Ahmad, Muhammad; Khan, Muddasir Ahmad; Khan, Abdus Sattar (Journal of Postgraduate Medical Institute, 2011)
Objective: The study was designed to determine and compare the levels of both water soluble and fat soluble naturally occurring antioxidant vitamins, in order to know the antioxidant vitamin status of the type 1 diabetic and non-diabetic healthy individuals. Material and Methods: This case control study was conducted at Department of Chemistry, University of Peshawar from November 2004 to August 2005. Blood glucose, triglycerides, total cholesterol, HDL-c, LDL-c, VLDL-c and antioxidant vitamins (íŸ-Carotene, A, E, and C) levels were determined in 30 Type 1 diabetic and 30 healthy subjects. Results: Values of blood glucose and lipid parameters were observed to be significantly increased (P 0.001) with exception of HDL-c, which was significantly decreased (P 0.001) in Type 1 diabetic patients. The concentration of antioxidant vitamins (íŸ-carotene, E and C) were found to be significantly low in Type 1 diabetics when compared with normal healthy controls. Conclusion: Observation of low levels of antioxidant vitamins suggests possibly significant defects in antioxidant protection in Type 1 diabetes mellitus patients.